AB1241 Interstitial lung disease ultrasound evaluation in churg-strauss patients. (23rd January 2014) - Delle Sedie, A.; Baldini, C.; Latorre, M.; Pepe, P.; Riente, L.; Paggiaro, P.L.; Bombardieri, S.
Abstract : Background: Churg Strauss syndrome (CSS) is a systemic vasculitis characterized by asthma, eosinophilia and lung infiltrates. Ultrasound (US) has recently been used to study the lung and specific findings (called B-lines) have been related to the thicknening of the interlobular septa, making it possible to assess interstitial lung disease. The B-lines have also been related to a decrease of carbon monoxide diffusing capacity (DLCO) values[1]. Objectives: The aim of the study was to assess the usefulness of US in the assessment of lung involvement in a group of CSS patients. Methods: A group of consecutive outpatients affected by CSS (according to ACR criteria) were enrolled. Asthma severity was evaluated according to FEV1, FEV1/SVC, GINA guidelines, asthma control test. In all the cases, chest X-rays and DLCO were performed. Systemic clinical and serological disease manifestations, BVAS and VDI were assessed. Lung US was performed blindly by the same operator with a Toshiba Powervision 6000 machine and a 6 MHz linear probe, using a scanning protocol used in the previous studies [2]. Total score was given by the sum of the B-lines in each intercostal space. Results: Ninenteen patients (mean age 55.3±14.5 years, F:M=7:12, mean disease duration 6.9±7.1 years, ANCA positivity 32%) were enrolled. At study entry, all the patients were in clinical remission; asthma was poorly or partially controlled in 4 and 8 patients, respectively. Two patients showed persistent interstitial involvement on X-ray, which was confirmed on HRCT scan. Inhaled glucocorticoid (GC) and long-acting beta2-agonist were taken by all the patients. Fifteen subjects were on maintenance therapy with low-doses oral GC associated with methotrexate in 6/15 cases. B-lines total score was negative (<12) (2) in 15/19 patients (mean 4.1±3.4). A positive B-line total score was detected in 4/19 subjects (mean 38±32.3) including the 2 HRCT positive cases. Conclusions: These preliminary results emphasise the role of US in the assessment of lung interstitial involvement in CSS patients with the advantages of having a good prediction of disease damage and of the use of a radiation-free bed-side imaging technique. References: Gargani L, Doveri M, D'Errico L et al. Rheumatology (Oxford). 2009;48:1382-7 Delle Sedie A, Doveri M, Frassi F et al. Clin Exp Rheumatol 2010;28(5 Suppl 62):S54 Disclosure of Interest: None Declared